Fusicoccane glycosides from the endophytic fungus Talaromyces sp. DC-26 - Peng Zhou; Jingwen Yu; Xueying Deng; Jinyan Cai; Wenya Feng; Junjun Liu; Qin Li; Chong Dai; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2026)

Large-strain self-weight consolidation model under double-drained conditions: A unified framework incorporating water weight effects - Cong Mou; Jiaxing Weng; Feng Ji; Jianhua Wang; Junjun Ni; Dechang Ren; Jin Yu (Transportation Geotechnics, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

Microwave digestion-ICP-MS coupled with molecular docking: unraveling elemental distribution and its correlation with glucose and fructose accumulation in 25 strawberry cultivars - Jiayue Xu; Hao Chen; Yang Ni; Yingying Zhang; Junjun Yang; Chen Feng; Guixia Wang; Rong Xiong (Food Chemistry, 2026)

Enzymatically synthesized native-like guaiacyl dehydrogenation polymer as a formaldehyde-free adhesive for high-strength, water-resistant plywood - Rui Luo; Wenhao Liu; Qian Tu; Yuanpu Wang; Junjun Chen; Junxian Xie; Rong Zhang; Nianjie Feng; Peng Wang (Chemical Engineering Journal, 2026)

Low-frequency vibration-induced crack expansion: Insights from resonance frequency and amplitude effects - Junjun Feng; Ting Zhang; Wangyuan Liu; Xinyu Zhang; Yankun Ma; Xiaofei Liu (Gas Science and Engineering, 2026)

Animal gut microbes and microbiomes in the 21st century and beyond - Zhigang Zhang; Feng Jiang; Zhipeng Li; Limei Lin; Bin Qi; Dandan Han; Chao Ran; Shengyong Mao; Junjun Wang; Zhigang Zhou; Min Wang; Jilian Li; et al. (Science China Life Sciences, 2026)
Animal gut microbiomes—comprising bacteria, archaea, fungi, viruses, and protozoa—are fundamental to host evolution, physiology, and ecosystem resilience. This review synthesizes 21st-century advances in their diversity, spatiotemporal dynamics, and functional roles across the animal kingdom. Although high-throughput metagenomics has transformed the field, major biases remain: most studies still focus on domesticated vertebrates and fecal samples, leaving substantial “microbial dark matter” in wild hosts, invertebrates, and non-bacterial domains unexplored. We highlight how gut microbiomes mediate adaptation to environmental extremes, including hypoxia, temperature stress, and toxins, and how industrialization disrupts these communities, contributing to biodiversity loss and disease risk. We further integrate eco-evolutionary theory, multi-omics, and spatial modeling to clarify cross-kingdom interactions and functional networks. Finally, we discuss translational applications—including probiotics, fecal microbiota transplantation (FMT), phage therapy, and synthetic consortia—and emphasize the need for global collaborative initiatives, artificial intelligence (AI)-driven discovery, and standardized databases to unlock the full potential of animal gut microbiomes for biodiversity conservation, climate resilience, and planetary health in the coming decades.

From single-interface LN2 fracturing to CBM stimulation: Temperature optimization and cracking mechanism - Junjun Feng; Hongqing Qiu; Peng Zhang; Wei Li; Xiaofei Liu; Yankun Ma (Fuel, 2026)

Assessment of ultrasonic vocalization-mediated communication deficits in AD rats: A social learning paradigm using conspecific drinking behavior - Xinxiang Su; Junjun Pu; Jinxia Liao; Yuqian Tang; Liting Feng; Zhen Wu (Behavioural Processes, 2026)

Erosion processes of lahar travelling on volcanic sediments: Insights from the physical and numerical modeling - Shengwu Qin; Jiangfeng Lv; Shuangshuang Qiao; Junjun Chen; Feng Wan; Jingyu Yao; Guangjie Li; Lingshuai Zhang (CATENA, 2025)

Challenges of high temperature on ultrasonic propagation in coal reservoirs: Insights from moisture desorption and fissure expansion - Junjun Feng; Shigeng Li; Yankun Ma; Yuanfang Qu; Qisong Huang; Houcheng Ding (Gas Science and Engineering, 2025)

Characteristic aroma identification of differentially colored peach fruits based on HS-SPME-GC–MS - Chen Feng; Yang Ni; Yingying Zhang; Junjun Yang; Rong Xiong (Food Chemistry, 2025)

Coupling effect of moisture desorption and matrix contraction on resistivity of water-bearing coal under high geothermal environment - Junjun Feng; Yuanfang Qu; Shigeng Li; Chuanhua Xu; Yankun Ma; Qisong Huang; Long Dang (Journal of Applied Geophysics, 2025)

Distribution characteristics, source analysis and ecological risk assessment of PAHs in tea garden soil in China - Jinzhi Li; Jiantao Xue; Yan Tan; Mingmin Jia; Junjun Feng; Xueqing Feng; Ningguo Zheng; Haoxin Fan; Huaiying Yao (Environmental Research, 2025)

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Amylopectin from maize-derived carbonized polymer dots as a novel high-efficiency antioxidant for periodontitis treatment - Junjun Liu; Naibo Feng; Xinyu Jiang; Xirui Xin; Yubo Hou; Zhende Jiang; Laijin Lu; Weixian Yu; Bai Yang (Chemical Engineering Journal, 2024)

Abnormal percent amplitude of fluctuation in patients with lifelong premature ejaculation is associated with neurotransmitter profiles - Jiarui Yuan; Pinxiao Wang; Dingxin Nie; Wanxiang Zheng; Kepu Liu; Jianyong Feng; Yuntao Zhang; Yanzhu Wang; Junjun Gao; Ming Gao (Brain Imaging and Behavior, 2024)

Effects of bed pumice content on lahar erosion: An example from Changbaishan volcano, China - Shengwu Qin; Jiangfeng Lv; Shuangshuang Qiao; Junjun Chen; Jingyu Yao; Feng Wan; Shuaiying Peng; Gohar Rehman; Xiaowei Liu (Engineering Geology, 2024)

Diversity and influencing factors of microbial communities in rhizosphere and nonrhizosphere soils of tea plant - Junjun Feng; Mingmin Jia; Yan Tan; Hongwen Yue; Xueqing Feng; Ningguo Zheng; Juan Wang; Jiantao Xue (Journal of Soils and Sediments, 2024)

Path analysis of digital development on the green industrial transformation of Chinese resource-based enterprises - Qi Zhao; Ming Guo; Fangfang Feng; Junjun Li; Hangtian Guan (Resources Policy, 2024)

First identification and molecular subtyping of Blastocystis in free-living wild birds from urban Xinxiang, China - Tiantian Li; Huimei Feng; Yingxu Zheng; Junjun Lv; Chi Zhang; Xuefeng Yang; Xuehan Liu (Veterinary Research Communications, 2023)

Energy optimal depth control for multimodal underwater vehicles with a high accuracy buoyancy actuated system - Junjun Cao; Rui Lin; Chunhu Liu; Hao Feng; Caoyang Yu; Baoheng Yao; Lian Lian (Ocean Engineering, 2023)

Quantitative assessment of the effects of zeolite alteration processes on deep clastic reservoirs – A case study of the Jiamuhe Formation in the Shawan Sag, Junggar Basin, China - Junjun Zhou; Haiguang Wu; Jian Wang; Guang Hu; Yunfeng Zhang; Jinlai Feng; Yilin Li (Marine and Petroleum Geology, 2023)

Positive and negative effects of marine transgression on the quality of lacustrine source rocks in the Upper Cretaceous Songliao Basin, China - Haiguang Wu; Chengcheng Feng; Xun Kang; Dawei Fu; Jinlai Feng; Yunfeng Zhang; Junjun Zhou; Tianxin Hu (Marine and Petroleum Geology, 2023)

Changes in soil organic carbon stability in association with microbial carbon use efficiency following 40 years of afforestation - Qianxi Li; Wei Jia; Junjun Wu; Lingling Wang; Feng Huang; Xiaoli Cheng (CATENA, 2023)

Covalent-crosslinking IRMOF-3-NH2/PVC ultrafiltration membrane for simultaneous removal of bisphenol A and Cd2+ ions in water - Yong Pan; Wei Huang; Yong Zhou; Feng Liu; Chen Zhu; HaiXia Pang; JunJun Tan; BaoMing Xu (Journal of Cleaner Production, 2023)

Response of partial nitritation/anammox granules to biodegradable organic input in bacterial community and functions - Feiyue Qian; Yaru Liu; Chenyun Mo; Huan Zhang; Feng Yan; Junjun Gao; Jinlong Zhuang (Journal of Water Process Engineering, 2023)

Rainfall interception measurements and modeling in a semiarid evergreen spruce (Picea crassifolia) forest - Junjun Yang; Zhibin He; Jianmin Feng; Pengfei Lin; Jun Du; Lingxia Guo; Yufeng Liu; Jialiang Yan (Agricultural and Forest Meteorology, 2023)

Distinctive Roles of Wnt Signaling in Chondrogenic Differentiation of BMSCs under Coupling of Pressure and Platelet-Rich Fibrin - Baixiang Cheng; Fan Feng; Fan Shi; Jinmei Huang; Songbai Zhang; Yue Quan; Teng Tu; Yanli Liu; Junjun Wang; Ying Zhao; Min Zhang (Tissue Engineering and Regenerative Medicine, 2022)

Determination of basic friction angle of three planar rock joints - Jun Peng; Zhicheng Tang; Chuanhua Xu; Di Hou; Qisong Huang; Junjun Feng (Arabian Journal of Geosciences, 2022)

Effects of Acid Sulfate and Chloride Ion on the Pore Structure and Mechanical Properties of Sandstone Under Dynamic Loading - Xiaoliang Li; Zhentang Liu; Xiaojun Feng; Huajie Zhang; Junjun Feng (Rock Mechanics and Rock Engineering, 2021)

How do Biotic and Abiotic Factors Regulate Soil Enzyme Activities at Plot and Microplot Scales Under Afforestation? - Qianxi Li; Ji Chen; Jiao Feng; Junjun Wu; Qian Zhang; Wei Jia; Qiaoling Lin; Xiaoli Cheng (Ecosystems, 2020)

Contrasting soil C and N dynamics inferred from δ13C and δ15N values along a climatic gradient in southern China - Jiao Feng; Fan Yang; Junjun Wu; Qiong Chen; Qian Zhang; Xiaoli Cheng (Plant and Soil, 2020)

Soil labile and recalcitrant carbon and nitrogen dynamics in relation to functional vegetation groups along precipitation gradients in secondary grasslands of South China - Adugna Feyissa; Fan Yang; Jiao Feng; Junjun Wu; Qiong Chen; Xiaoli Cheng (Environmental Science and Pollution Research, 2020)

Loop-mediated isothermal amplification-lateral-flow dipstick (LAMP-LFD) to detect Mycoplasma ovipneumoniae - Jie Zhang; Junjun Cao; Mingsong Zhu; Mingguo Xu; Feng Shi (World Journal of Microbiology and Biotechnology, 2019)

Mapping soil organic carbon stocks of northeastern China using expert knowledge and GIS-based methods - Xiaodong Song; Feng Liu; Bing Ju; Junjun Zhi; Decheng Li; Yuguo Zhao; Ganlin Zhang (Chinese Geographical Science, 2017)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Analysis of finite element method on mechanical properties of wheat kernel - Feng Jia; Jinshui Wang; Pei Fan; Haicheng Yin; Junjun Guan; Mengqing Zhou (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Preliminary genetic linkage maps of Chinese herb Dendrobium nobile and D. moniliforme - SHANGGUO FENG; HONGYAN ZHAO; JIANGJIE LU; JUNJUN LIU; BO SHEN; HUIZHONG WANG (Journal of Genetics, 2013)